Logic, Theology and Poetry in Boethius, Anselm, Abelard, and Alan of Lille - Sweeney, E. author. aut Link
XII, 236 p.
Keywords: This interdisciplinary study offers an interpretation of the major logical, philosophical/theological and poetic writings of Boethius, Abelard and Alan of Lille. The author examines their theories of language and the ways in which they explore how words illuminate things, how the mind comprehends God and how the individual reaches beatitude.